ACTIVITY AND DOCUMENT SUPPORT OF UNIVERSITIES IN INFORMATION SOCIETY - Shelestova, Anna M. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
This article is devoted to the universities as information centers and changes that are occurred there due to certain trends in development of information society.